Aspects of bronze age metalwork in northern East Anglia - Pendleton, Colin F. (1992)
The bronze age metalwork of northern East Anglia is well known, both for its quality and quantity. The main concentration occurs along the south-eastern fen edges which are recognised as one of the primary centres of metalwork in Britain. Due to the 'wet' nature of the fenland the metalwork from the area has formed one of the main supports for the belief, over the last 25 years, in a practice of bronze age wetland ritual or votive deposition. The main theme of this work examines this important issue. The fenland material has not been isolated but is put into a regional context by the examination of other finds from northern East Anglia.